Disclosure Effects in the Laboratory: Liquidity, Depth, and the Cost of Capital - Bloomfield, Robert J.; Wilks, T. Jeffrey (The Accounting Review, 2000)
Greater disclosure quality leads to higher prices and greater liquidity in a laboratory financial market, and these effects are stronger when investors face the risk of unpredictable demand shocks. These results are consistent with a broad class of theoretical and empirical studies. Disclosure has larger effects on prices and liquidity at greater market depths. We conclude that archival studies looking only at quoted transaction prices and spreads (which typically pertain to small transactions) may underestimate the potential importance of disclosure on larger transactions that occur at greater market depths.